CORRECTION OF BIOCHEMICAL MARKERS OF ANTIMICROBIAL DEFENSE AND BACTERIAL CONTAMINATION IN RAT GINGIVA INDUCED BY A MODEL OF PEROXIDATIVE PERIODONTITIS AND ALIMENTARY PROTEIN DEFICIENCY USING A THERAPEUTIC-PROPHYLACTIC COMPLEX - Hurtova, Y.M.; Shnaider, S.A.; Dienha, O.V.; Kosenko, D.K.; Topov, I.H.; Goncharuk, S.V.; Syroishko, M.V. (World of Medicine and Biology, 2025)
The study assessed the impact of a newly developed therapeutic-prophylactic complex on indices of nonspecific antimicrobial defence (lysozyme activity) and bacterial contamination (urease activity, dysbiosis index) in gingival homogenates of rats subjected to a combined model of peroxidative periodontitis and alimentary protein deficiency. Thirty male Wistar rats were randomly assigned to three groups: an intact control, a combined-pathology group, and a combined-pathology group treated with the therapeutic-prophylactic complex. The therapeutic-prophylactic complex effectively prevented disruptions of antimicrobial homeostasis and substantially restored the microbiological balance of periodontal tissues under conditions of protein-oxidative stress, underscoring its potential as a prophylactic agent for nutrition-related periodontal injuries.
Keywords: periodontitis; protein deficiency; rats; experiment; biochemical markers